Determinants of Pre-Diabetes on Teenagers in Palangka Raya City - Sylvia, Ester Inung; Datak, Gad; Ardiyani, Visia Didin (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Pre-diabetes is a stage prior to diabetes mellitus (DM) and many studies in west countries found the risk factors of diabetes were mostly related to the nutri onal status of being overweight and obese. Dia- betes mellitus is not only experienced by adults but also by teenagers. They have the poten al for pre-diabetes because they may have unhealthy lifestyles such as smoking, consuming alcohol, high-calories, and junk foods and lack of physical ac vity. This study aims to determine the risk factors of pre-diabetes among senior high school students in Palangka Raya, Central Kalimantan, Indonesia. Methods: This study was a qualita ve study using a ques onnaire as an instrument for data collec on. It consists of a set of ques ons on diabetes risk. This research conducted in four public senior high schools in Palangka Raya with the total sample was 131 respondents have par cipated in this research. Results: 25 respondents (19.1%) from a total sample of 131 par cipants suffered from pre-diabetes and 30.5% of respondents had a family with DM. Some students (6.9%) had a smoking habit and 13% incidence of pre- diabetes in high school students related to these factors (R2: 0.13). Only less than half of the total respondents (43.5%) had a normal BMI. As many as 39.7% of respondents were undernourished while the rest were over- weight. Conclusion: Pre-diabetes factors on teenagers in Palangka Raya are female dominate had a history of DM, and being overweight. This study further leads to the importance of weight control that focusing on physical ac vity and dietary management as early precau ons. Health educa on is required to suppress the number of risk fac- tors for diabetes.